Effect of lensing magnification on type Ia supernova cosmology. Issue 3 (2nd May 2019) - Sakakibara, Hinako; Nishizawa, Atsushi J; Oguri, Masamune; Tanaka, Masayuki; Hsieh, Bau-Ching; Wong, Kenneth C
ABSTRACT: Effect of gravitational magnification on the measurement of distance modulus of type Ia supernovae is presented. We investigate a correlation between magnification and Hubble residual to explore how the magnification affects the estimation of cosmological parameters. We estimate magnification of type Ia supernovae in two distinct methods: one is based on convergence mass reconstruction under the weak lensing limit and the other is based on the direct measurement from galaxies distribution. Both magnification measurements are measured from Subaru Hyper Suprime-Cam survey catalogue. For both measurements, we find no significant correlation between Hubble residual and magnification. Furthermore, we correct for the apparent supernovae fluxes obtained by Supernova Legacy Survey 3-yr sample using direct measurement of the magnification. We findΩ _m0= 0.282 ^+0.109 _-0.086 andw = -1.132 ^+0.571_-0.340 for supernovae samples corrected for lensing magnification when we use photometric redshift catalogue ofMizuki, whileΩ _m0= 0.267 ^+0.114 _-0.088 andw = -1.074 ^+0.504 _-0.312 forDEmP photo- z catalogue. Therefore, we conclude that the effect of magnification on the supernova cosmology is negligibly small for the current surveys; however, it has to be considered for the future supernova survey like LSST.